COMPARATIVE ANALYSIS OF SOME PHENOLIC ACIDS OF IN VITRO AND IN VIVO GROWN PLANT LEAVES OF SALVIA HISPANICA - & Al- Dabagh, Salih (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Several plant species could be produce bioactive compounds, which play a key role in protecting human health, Chia is one of these plant species which has been gaining growing popularity among the traditional medicine groups. In order to sustainably produce plant biomass and its phytochemical content. Numerous biotechnological approaches need to be employed, and elicitation has proven to be a very effective method for increased secondary metabolite production in various in vitro culture. The current research involves the application of various concentrations of SA as an elicitor with 2,4-D and BAP in callus cultures, and the main aim was to stimulate the accumulation of biomass and phytochemical contents. The results showed that the highest concentration of keamferol and gallic acid compounds in callus of S. hispanica were occurred in the treatment with 2 mgl-1 2,4-D and 2mgl-1 SA in the presence of 0.5mgl-1 BA.